Pengaruh Pengukuran Efektivitas Organisasi Dengan Pendekatan Model MC Kinsey7s Framework Terhadap Kinerja Pegawai SMK Negeri Karangpucung - Sri Hamidahningrum; Apri Budianto; Ferey Herman (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The research was conducted with the aim of determining the influence of organizational effectiveness using the Mc Kinsey 7s Framework Model Approach on Employee Performance. The problem formulation proposed in this research is How Organizational Effectiveness with the McKinsey 7S Framework Model Approach Influences the Performance of Karangpucung State Vocational School Employees. The research method used is a descriptive quantitative method with a questionnaire distribution method. Data collection techniques in this research are literature study and field study. Meanwhile, the technical data analysis used by the author in this research is by distributing questionnaires. From the research results it was found that: The results of the research on measuring organizational effectiveness using the McKinsey 7S Framework Model Approach have a positive and significant effect on performance, meaning that if measuring organizational effectiveness using the McKinsey 7S Framework Model Approach increases, it will have an effect on performance.